Peran Sistem Pengendalian Manajemen dalam Meningkatkan Akurasi Laporan Keuangan melalui Implementasi Digital Accounting pada UMKM di Kota Bandung - Rony Tarigan; Se Tin Se Tin (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2025)
This study aims to analyze the role of management control systems in improving the accuracy of financial reports through the implementation of digital accounting in MSMEs in Bandung City. In the digitalization era, the use of accounting technology continues to evolve to enhance financial recording efficiency and support more accurate decision-making. This research adopts a quantitative method. The data used in this study are primary data collected through online questionnaires distributed via Google Form. The data analysis technique employed is Partial Least Square (PLS) using SmartPLS 3 software, with a total of 100 MSMEs respondents in Bandung City. The findings indicate that an effective management control system, supported by the implementation of digital accounting, significantly contributes to improving the accuracy of financial reports and the effectiveness of managerial control in business decision-making.